Using Google forms in E-ESL classrooms during COVID-19 pandemic: undergraduates’ perspectives / Kimberley Lau Yih Long, Christine Jacqueline Runggol and Jacqueline Susan Rijeng - Kimberley, Lau Yih Long; Runggol, Christine Jacqueline; Rijeng, Jacqueline Susan (Universiti Teknologi MARA Cawangan Kedah, 2023)
The use of technology in language learning has become increasingly prevalent in recent years, with many educators integrating various digital tools into their teaching practices. One such tool is Google Forms, which allows for the creation of interactive and engaging lessons. This study highlighted undergraduates’ perceptions on using Google Forms as an instructional tool in E-ESL classrooms. It implemented a quantitative approach whereby undergraduates filled in an e-questionnaire which consisted of open and closed-ended questions upon completing six grammar lessons of Integrated Language Skills 1 (ELC121) which was administered with Google Forms. The questionnaire received 97 responses from undergraduates of four first year Diploma programs (two Social Sciences and two Applied Sciences). The purpose of this study was to explore undergraduates’ perceptions of using Google Forms as an instructional tool to teach grammar in E-ESL classrooms. It also aimed to analyze their opinions on the positive aspects of the instructional tool and identify their opinions on aspects which needed to be improved. Results showed that undergraduates have positive perceptions on using Google Forms as a grammar teaching tool in E-ESL classrooms. In terms of the positive aspects of Google Forms lessons, most of them found the lessons to be fun (53%) and new to them (23.4%). On the other hand, undergraduates wanted the lessons to be improved by adding in more games (21.4%) and quizzes (17.9%) despite 50% of them finding it to be already good. Findings from this study provide a basis for educators to develop effective teaching tools for English online classrooms in Sarawak, Malaysia.